Finding my passion: a compilation of an internship for the Arc of Sedgwick County - Frantz, Courtney (My University, 2015)
The most valuable jobs are the ones that not only teach transferrable professional skills such as working within a budget or scheduling meetings, but that also spark a passion that is carried with you for the rest of your life. The Arc of Sedgwick County is one of those rare jobs. I worked in the YESS program which stands from Youth Education and Socialization Skills. For a more comprehensive summary, it is a summer day camp for youth with special needs focusing on educational aspects in the morning and community integration in the afternoon. In addition to YESS, I also got to work with the Circle of Friends program which is a social inclusion initiative in schools throughout the Wichita community. Both of these programs are unique and provide important avenues for the special needs population in Wichita to not only gain life skills but also have a more fulfilling life. Throughout this summer, I have been fortunate enough to gain important professional skills as well as develop a deeper passion for serving those with special needs in a variety of ways.
Sponsored by the Marjorie J. and Richard L.D. Morse Family and Community Public Policy Scholarship
Citation: Frantz, C. (2012). Finding my passion: a compilation of an internship for the Arc of Sedgwick County. Unpublished manuscript, Kansas State University, Manhattan, KS.
Keywords: Arc of Sedgwick County; Educational planning--Kansas; Children with disabilities--Education--Kansas--Sedgwick County; Teenagers with disabilities--Education--Kansas--Sedgwick County; Reports; Reports